Incidence, mortality, and survival analyses of patients with thymic lymphoma - Wang, Li; Wang, Zhile; Huo, Lanqing; Zhao, Ailin (Frontiers in Oncology, 2022)
Objectives To explore the clinical and prognostic characteristics of thymic lymphoma and the effects of current treatments on the prognosis. Methods Patients diagnosed as primary thymic lymphoma between 1975 and 2018 from the nine states of the US were identified, including Atlanta, Connecticut, Detroit, Hawaii, Iowa, New Mexico, San Francisco-Oakland, Seattle–Puget Sound, and Utah. Incidence and mortality rates were analyzed using SEER*Stat 8.3.9 software. Univariate and multivariate Cox regressions were performed to identify prognostic factors. The Kaplan–Meier curve and log-rank test were used to compare overall survival (OS) among different treatments. Results A total of 233 patients diagnosed as thymic lymphoma were identified, and eight of them were lost to follow-up or died upon diagnosis. The incidence of thymic lymphoma was 2.032 per ten million (95% CI: 1.777–2.312), and the mortality rate was 0.649 per ten million (95% CI: 0.508–0.817). Among the 225 patients with definite follow-up, 98 were males and 127 were females, with a median age of 33 years. The Cox regression results showed that age and pathological type were independent risk prognostic factors. The 5-, 10-, and 20-year OS were 80.0%, 77.5%, and 70.9%, respectively. For Ann Arbor stage I and II patients, there was no significant difference between the surgical group (N = 78) and the non-operative group (N = 65; P = 0.270). The radiotherapy group (N = 79) had better OS than the non-radiotherapy group (N = 64) in the first 25 years, and the prognosis in the later years was not significantly different (P = 0.051). The chemotherapy group (N = 37) had a significantly better prognosis than the non-chemotherapy group (N = 37; P = 0.020). Patients who received postoperative radiotherapy (N = 45) or who only received radiotherapy (N = 34) seemed to have better OS than that of patients who only received surgery (N = 33), although the difference was not significant (P = 0.063). Conclusions Age and pathological type were independent prognostic factors for thymic lymphoma. Surgical treatment had limited effects on OS, while both radiotherapy and chemotherapy could significantly improve the survival outcome.